First complete mitogenome assembly of Castanea sativa: structure, comparative genomics, and phylogeny - Villa, Sara; Marchesini, Alexis; Torre, Sara; Bianco, Luca; Fontana, Paolo; De Quattro, Concetta; Moser, Mirko; Piazza, Stefano; Alessandri, Sara; Pavese, Vera; Pollegioni, Paola; Vernesi, Cristiano; et al. (Tree genetics & genomes, 2025)
The sweet chestnut ( Castanea sativa Mill.) is one of the most widespread cultivated temperate trees in Europe, valued both for its edible nuts and high-quality timber. Due to its ecological, economic, and cultural importance, it has been the focus of extensive genetic studies. However, its mitochondrial genome has remained largely unexplored. Here, we present the first complete mitochondrial genome of C. sativa (cultivar ‘Marrone di Chiusa Pesio’), assembled using high-throughput sequencing and characterised through comparative analyses with closely related species. The final assembly consists of six contigs with a total length of 402,729 bp, comprising 35 protein-coding genes, 33 tRNA genes, and 3 rRNA genes. Compared to the congeneric C. mollissima , C. sativa shows a relatively low repeat content in terms of both number and length. Codon usage patterns were found to be highly similar among C. sativa , C. mollissima , and C. henryi . Additionally, homologous fragments between the plastid and mitochondrial genomes were identified, totaling 4,671 bp (1.16% of the mitogenome), and including several tRNA genes. A phylogenetic analysis based on mitochondrial coding sequences from C. sativa and 11 other Fagaceae species confirmed its close relationship with C. mollissima , C. henryi , and Castanopsis carlesii . Discrepancies observed among mitochondrial, plastid, and nuclear gene trees likely reflect either inherent genomic characteristics or extensive hybridisation, particularly within the genus Quercus.